Extrapolation of Efficacy and Dose Selection in Pediatrics: A Case Example of Atypical Antipsychotics in Adolescents With Schizophrenia and Bipolar I Disorder. (29th June 2021) - Kalaria, Shamir N.; Farchione, Tiffany R.; Uppoor, Ramana; Mehta, Mehul; Wang, Yaning; Zhu, Hao
Abstract: Pediatric labeling information for novel atypical antipsychotics can be significantly delayed as the result of time lag between initial drug approval in adults and the completion of pediatric clinical trials. This delay can lead health care providers to rely on limited evidence‐based literature to make critical therapeutic decisions for pediatric patients. Effective and scientifically justified dosing recommendations are needed to improve treatment outcomes in pediatric patients with schizophrenia and bipolar I disorder. Extrapolation‐based drug development strategies rely on leveraging prior data to reduce evidentiary requirements for newer data in establishing drug efficacy. On January 13, 2020, the US Food and Drug Administration (FDA) released a general advice letter to sponsors highlighting the acceptance of extrapolating efficacy of atypical antipsychotics to pediatric patients. This review provides insight into the FDA's justification for extrapolating efficacy from adult to pediatric patients and provides a rationale for dose selection in pediatric patients with schizophrenia and bipolar I disorder.